African drama and performance - Conteh-Morgan, John; Olaniyan, Tejumola (African expressive cultures., 2004)
This title explores the diversity of the performing arts in Africa and the diaspora, from studies of major dramatic authors and formal literary dramas to improvisational theatre and popular video films.